On the killing of mycobacteria by macrophages - Jordao, Luisa (2008)
Both pathogenic and non-pathogenic mycobacteria are internalized into macrophagephagosomes. Whereas the non-pathogenic types are invariably killed by allmacrophages, the pathogens generally survive and grow. Here, we addressed thesurvival, production of nitrogen intermediates (RNI) and intracellular trafficking of thenon-pathogenic M. smegmatis, the pathogen-like, BCG and the pathogenic M. bovis indifferent mouse, human and bovine macrophages. The bacteriocidal effects of RNI wererestricted for all bacterial species to the early stages of infection. EM analysis showedclearly that all the mycobacteria remained within phagosomes even at late times ofinfection. The fraction of BCG and M. bovis found in mature phagolysosomes rarelyexceeded 10 % of total, irrespective of whether bacteria were growing, latent or beingkilled, with little correlation between the extent of phagosome maturation and thedegree of killing. Theoretical modelling of our data identified two different potentialsets of explanations that are consistent with our results. The model we favour is one inwhich a small but significant fraction of BCG is killed in an early phagosome, thenmaturation of a small fraction of phagosomes with both live and killed bacteria,followed by extremely rapid killing and digestion of the bacteria in phago-lysosomes.